Hematoma espontâneo do músculo reto abdominal - Valentim,Leonardo Fernandes (2005)
Spontaneous hematoma of the rectus sheath is a rare entity, which may be confused with the surgical causes of acute abdomen. We present a well succeeded conservative therapy in a woman in the 7th decade of life.